Prispevek k poznavanju flore Čateža pri Trebnjem (vzhodna osrednja Slovenija) - Bačič, Tinka (Natura Sloveniae, 2000)
During the Youth Research Camp Čatež '97, floristical group was mapping vascular plants in 2 quadrants of the MTB grid (0055/2 and 0055/4). The artidediscusses the results of this research and presents some of the most interesting recorded species: Geranium pyrenaicum, Nigella damascena, Coriandrum sativum, Lepidium virginicum, Spergularia salina, Euphorbia nutans in Euphorbia marginata.
Keywords: botanika; Čatež; Dolenjska; Ecosystem; flora; Lower Carniola; Plants; Rhododendron-Park Bremen